STUDENT AFFAIRS, SOCIAL DEVELOPMENT AND STUDENTS-EXTRACURRICULAR ACTIVITIES AT VORONEZH STATE UNIVERSITY - Oleg V. Grishaev (Высшее образование в России)
This article analyzes the organization of student affairs, social development and students' extracurricular activities of Voronezh State University, and particularly focuses on the development of students' self-government. The article shows examples of successful projects related to the activities of student organizations. One of the indicators of effective work in this area is the sustained support of the Ministry of Education and Science of the Russian Federation within the Programme for Student Community Development.